Pengaruh Love Of Money, Machiavellian, dan Equity Sensitivity Terhadap Persepsi Etika Penggelapan Pajak (Tax Evasion) - Asih, Ni Putu Sri Murtining; Dwiyanti, Kadek Trisna (E-Jurnal Akuntansi, 2019)
This study aims to know the influence of love of money, machiavellian, and equity sensitivity toward individual taxpayer’s ethical perception of tax evasion in east- denpasar tax office. Population in this study are whole registered individual- taxpayer in east-denpasar tax office.The number of samples used are 100 of 76543 active individual-tax payer that registered until 2017. The amount of samples were counted based on slovin with accidental sampling method. Data collection are conducted by questionnaire method in this study. Data analysis technique used is Multiple Linear Regression Analysis. The result of this studyindicates that love of money and machiavellian make negative effect on taxpayer’sethical perception of tax evasion, but equity sensitivity does not influence ontaxpayer’s ethical perception of tax evasion. Keywords : Love of money, machiavellian, equity sensitivity, ethical perception, tax evasion.